2022
DOI: 10.1155/2022/8939359
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Coracobrachialis, Biceps Brachii, and Pectoralis Minor Muscles and Their Correlation with Bifurcated Coracoid Process

Abstract: The aim of this study is to demonstrate the relationship between the proximal attachment of the coracobrachialis muscle and the short head of the biceps brachii and the distal attachment of the pectoralis minor. Their correlation with the bifurcated coracoid process (CP) will be also assessed. On the basis of these observations, a new classification of structures attached to the coracoid process is proposed. Classical anatomical dissection was performed on one hundred forty-five upper limbs. Three types of rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…It is no different in case we observed. The relationship between the origins of the shBB and CBM is also variable [ 33 ]. This case represents the most common combination of their origins (54%) and represents type I in the classification presented by Zielinska et al [ 33 ] (one head of the CBM and the shBB creating a common junction originating from the coracoid process).…”
Section: Discussionmentioning
confidence: 99%
“…It is no different in case we observed. The relationship between the origins of the shBB and CBM is also variable [ 33 ]. This case represents the most common combination of their origins (54%) and represents type I in the classification presented by Zielinska et al [ 33 ] (one head of the CBM and the shBB creating a common junction originating from the coracoid process).…”
Section: Discussionmentioning
confidence: 99%
“…The axillary artery and vein, long thoracic nerve, and brachial plexus are located nearby (52). Furthermore, one may see the presence of compound tendons originating from the short head of the biceps and coracobrachialis, together with the attachment of the pectoralis minor muscle (53). Burkhart suggests that in cases of partial tear of the subscapularis muscle, coracoplasty can be performed by establishing a window in the rotator interval.…”
Section: Treatmentsmentioning
confidence: 99%
“…To conduct the quality assessment of the identified studies, the Quality in Prognostic Studies Tool16’s four scales, including reporting and statistical analysis, study participation, outcome measurement, prognostic factor measurement, and confounding. Further, for each scale, a subscale was developed to enable the authors to grade the studies as low quality (0), intermediate quality [ 1 ], and high quality [ 2 ]. The quality assessment approach has been widely used by authors who have conducted systematic reviews and meta-analyses of variations of arteries and different body muscles [ 16 ].…”
Section: Reviewmentioning
confidence: 99%
“…The pectoralis minor anatomically offers the landmark to the much deeper structures that include the medial pectoral nerves, the axillary arteries, and the brachial plexus cords. Several anatomy studies and literature have reported variations with regard to the pectoralis minor muscle attachment points [1][2][3].…”
Section: Introductionmentioning
confidence: 99%